Serum and Salivary IgA, IgG, and IgM Levels in Oral Lichen Planus: A Systematic Review and Meta-Analysis of Case-Control Studies - Hamid Reza Mozaffari; Elisa Zavattaro; Abas Abdolahnejad; Pia Lopez-Jornet; Neda Omidpanah; Roohollah Sharifi; Masoud Sadeghi; Mohammad Shooriabi; Mohsen Safaei (Medicina, 2018)
Immunoglobulins (IgA, IgG, and IgM) are significant anti-inflammatory factors. The meta-analysis aimed to assess the serum and salivary levels of Igs as more important immunoglobulins in patients affected by oral lichen planus (OLP) compared to the healthy controls. Four databases, including PubMed/Medline, Scopus, Web of Science, and Cochrane Library as well as Iranian databases were checked up to January 2018 without language restriction. The quality of each involved study was done using the Newcastle⁻Ottawa Quality Assessment Scale (NOS) questionnaire. A random-effects model analysis was done by RevMan 5.3 software applying the mean difference (MD) plus 95% confidence intervals (CIs). The CMA 2.0 software was applied to calculate the publication bias among the studies. Out of 70 studies found in the databases, 8 studies were involved and analyzed in the meta-analysis. The meta-analysis included 282 OLP patients and 221 healthy controls. The pooled MDs of serum levels of IgA, IgG, and IgM were −0.13 g/L [95% CI: −0.24, −0.02; P = 0.02], 1.01 g/L [95% CI: −0.91, 2.93; P = 0.30], and −0.06 g/L [95% CI: −0.25, 0.14; P = 0.56], respectively; whereas, the salivary IgA and IgG levels were 71.54 mg/L [95% CI: 12.01, 131.07; P = 0.02] and 0.59 mg/L [95% CI: −0.20, 1.38; P = 0.14], respectively. Considering the few studies performed on saliva, the results suggested that the salivary levels, especially IgA level had higher values than the serum levels. Therefore, the salivary immunoglobulins can play a significant function in the OLP pathogenesis.